An Application of the Set Point Net Theory in Holy Qur'an: Pedagogic Contents in Surat ‘Yusuf’ and ‘Al-Qalam’ as an Example - Ababneh, Saleh Ahmad; Al-Rawajfeh, Aiman Eid; Al-Hanaktah, Isra'a Isam (Dirasat: Educational Sciences, 2020)
This study aims to apply the Set Point Net Theory on pedagogic contents in Surat ‘Yusuf’ and Surat ‘Al-Qalam’ as examples. The study applies a deductive approach which examines the text of the two Surahs. This approach offers a deeper look for understanding both the meaning and semantics of the text to deduce a pedagogic content. The results show that both Surahs ‘Yusuf’ and ‘Al-Qalam’ included pedagogic contents, such as planning, emotions, educational, ethical values, and social education. This is in addition to pedagogic strategies, such as dialogue, problem-solving, and journey techniques. Authors recommend that educational policies makers and curricula designers should include the meanings of symmetry. Future studies are recommended to develop the theory of the network of symmetry in the Qur’an in other educational areas.